A quality improvement project to improve pediatric medical provider sleep and communication during night shifts. (13th November 2018) - Loew, Megan; Niel, Kristin; Burlison, Jonathan D; Russell, Kathryn M; Karol, Seth E; Talleur, Aimee C; Christy, Leigh A N N; Johnson, Liza-Marie; Crabtree, Valerie M
Abstract: Quality problem or issue: Night-shift medical providers frequently experience limited sleep resulting in fatigue, often because of paging activity. Streamlined medical-specific communication interventions are known to improve sleep and communication among these providers. Initial assessment: We found that non-urgent paging communication occurred frequently during night-shifts, leading to provider sleep disturbances within our institution. We tested a quality improvement (QI) intervention to improve paging practices and determined its effect on provider sleep. Choice of solution: We used a Plan-Do-Study-Act QI model aimed at improving clinician sleep and paging communications. Implementation: We initially conducted focus groups of nurses and physician trainees to inform the creation of a standardized paging intervention. We collected actigraphy and sleep log data from physicians, nurse practitioners, and physician trainees and performed electronic collection of paging frequency data. Evaluation: Data were collected between December 2015 and March 2017 from pediatric residents, pediatric hematology/oncology (PHO) fellows, hospitalist medicine nocturnists and nurses working during night-shift hours in PHO inpatient units. We collected baseline data before implementation of the QI intervention and at 1 month post-implementation. Although objective measures and provider reports demonstrated improved medical-specific communication paging practices, provider sleep was not affected. Lessons learned: Provider-based standardization of paging communication was associated with improved medical-specific communication between nurses and providers; however, provider sleep was not affected. The strategies used in this intervention may be transferable to other clinics and institutions to streamline medical-specific communication.